The fallacy of beneficial ignorance: a test of Hirschman's Hiding Hand - Flyvbjerg, B (Elsevier, 2016)
Albert O. Hirschman's principle of the Hiding Hand stands stronger and more celebrated today than ever. The principle states that ignorance is good in planning, because if decision makers knew the real costs and difficulties of projects, few ventures would ever get started. The paper presents the first systematic test of the principle of the Hiding Hand, including a test of whether Hirschman's theory may be replicated with more and better data. This was found not to be the case. First, statistical tests reject the principle of the Hiding Hand at an overwhelmingly high level of significance (p < 0.0001). In reality, the exact opposite happens of what the principle states: instead of project success being secured by "creative error" and "beneficial ignorance"-where higher-than-estimated costs are outweighed by even higher-than-estimated benefits-the average project is in fact undermined by a double whammy of substantial cost overruns compounded by substantial benefit shortfalls. Second, Hirschman was found to have made the error of sampling on the dependent variable, undermining the validity of his findings. Third, Hirschman's sample of projects, on which he built his principle, is too small to support his wide conclusions. Fourth, Hirschman misrepresented his findings and misled his readers. In sum, the data do not support Hirschman's proposition that ignorance is good in planning. Ignorance is bad, if by bad we mean that ignorance leads to starting projects that should not have been started. Finally, the data also do not support an interpretation of Hirschman as an early behavioral economist, as proposed by Sunstein. Hirschman was a victim, not a student, of bias.